1981
DOI: 10.1128/aem.42.2.272-276.1981
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Rhizobium japonicum Strains at Temperatures Above 27°C

Abstract: A study was conducted to examine the growth responses of different Rhizobium japonicum strains to increasing temperatures, determine the degree of variability among strains in those responses, and identify temperature-related growth characteristics that could be used to select temperature-tolerant strains. Each of 42 strains was grown in liquid culture for 96 h at 19 incubation temperatures ranging from 27.4 to 54.1°C in a temperature gradient apparatus. Growth was estimated by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
1
7
0
1
Order By: Relevance
“…Taking into account several studies showing that strains' endurance to high temperatures in a culture medium correlates with their symbiotic performance under heat stress (Munevar & Wollum, 1981b; Rahmani et al ., 2009), the thermotolerant chickpea rhizobia identified in the present work could have potential agronomical importance. For example, isolate PMI‐1‐Portimão has a high symbiotic effectiveness (>75%) and is among the isolates with higher tolerance to all the tested conditions; hence, it represents a good candidate for field inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account several studies showing that strains' endurance to high temperatures in a culture medium correlates with their symbiotic performance under heat stress (Munevar & Wollum, 1981b; Rahmani et al ., 2009), the thermotolerant chickpea rhizobia identified in the present work could have potential agronomical importance. For example, isolate PMI‐1‐Portimão has a high symbiotic effectiveness (>75%) and is among the isolates with higher tolerance to all the tested conditions; hence, it represents a good candidate for field inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum temperature range for most rhizobia is 25–31 °C (Somasegaran & Hoben, 1994) and the upper temperature limits are between 32 and 47 °C (Munevar & Wollum, 1981a; Karanja & Wood, 1988). However, these limits vary among species and strains.…”
Section: Introductionmentioning
confidence: 99%
“…EPS analysis. Culture supernatants from YEM-grown, stationary-phase cells were concentrated by lyophilization (30). The optimum growth temperature was the temperature at which the highest growth rate (as measured by a change in the optical density) was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature affected the viability of water-stored rhizobia in generally the same manner as found for rhizobia stored in other ways. Earlier studies showed that most R. japonicum strains do not survive temperatures of 40°C either in peatbased inocula (5) or in liquid culture (20).…”
Section: Vol 47 1984mentioning
confidence: 99%